Peningkatan Pengetahuan Ergonomi Dan Kesehatan Lingkungan Pada Siswa Di Man 2 Bireun - Siregar Anggi Pramono; Ulhaq Muhammad Zia; Azzahra Raudha; Ulfa Mahlia; Humayra; Halim Amanda Dwinata; Amna Nadila; Murida Eva; Afra Nurul; Natasya Dea (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
School environmental health is an effort aimed at improving, realizing and developing the health status of students optimally. However, there are still many students who do not really care about environmental problems so that they have not yet manifested themselves in real action. Ergonomics is a systematic science, which uses data regarding the characteristics, limitations and abilities of humans in designing a work system, so that humans can work in the system optimally, in the sense of good, safe, comfortable, precise, simple and satisfying. In carrying out this activity, of course we want everything to be done well, quickly, safely, healthily, easily, easily, with maximum results and provide satisfaction. The problem in this research is that the level of students' understanding of ergonomics regarding the health of the school environment at MAN 2 Bireun is not yet known. The purpose of this research aims to determine the level of understanding of ergonomics and environmental health of students regarding the health of the school environment at MAN 2 Bireun. This research uses a cross sectional approach. The population in this study was all 12th grade students at MAN 2 Bireun, totaling 70 students. The sampling technique uses a formula from Slovin. The number of samples was 30 students, namely: XII IPS totaling 3 students, XII IPA I totaling 11 students, XII IPA 2 totaling 7 students, XII IPA 3 totaling 9 students. The data source used is primary data with data collection methods in the form of interviews with questionnaire instruments. The research results showed that the level of knowledge of class XII students at MAN 2 Bireun regarding ergonomics and school environmental health had a high level of knowledge.